Uzbek, Persian, Russian and English alternatives of wise words used in "Nazm ul-Javahir" - Nargiza Azimbayeva (Peerian Journals Publishing, 2023)
In this article, we will talk about the words of wisdom used in the work “Nazm ulJavahir” and their alternatives found in other languages. We will analyze their meaning, artistry, mutuality and unifying aspects.
Keywords: exemplary words; humanity; alternative